INJURY PREVENTION AND RECOVERY STRATEGIES FOR HIGH-LEVEL FEMALE FREESTYLE WRESTLERS - Primbetov Azamat Auyesbayevich (Journal Park Publishing, 2023)
In the physically demanding world of female freestyle wrestling, injury prevention and effective recovery strategies are paramount to maintaining peak performance and sustaining a successful career. This article delves into the unique challenges faced by high-level female freestyle wrestlers and explores evidence-based strategies aimed at preventing injuries, promoting rapid recovery, and ensuring long-term athlete well-being. By drawing from the expertise of sports medicine professionals, elite athletes, and coaches, we provide a comprehensive overview of injury prevention techniques and recovery protocols tailored to the specific demands of this rigorous sport. The insights presented herein are intended to serve as a valuable resource for female freestyle wrestlers, coaches, and sports healthcare providers, contributing to the overall betterment of the sport and the athletes who compete at its highest levels.
Keywords: Female Freestyle Wrestling, Injury Prevention, Recovery Strategies, Sports Medicine, Athlete Well-being, High-Level Performance, Wrestling Injuries, Sports Rehabilitation, Elite Athletes, Injury Management.